Accounting and Finance Literacy: A Comparative Study - ÇATIKKAŞ, ÖZGÜR (My University, 2019)
The aim of this study is to measure the accounting and finance literacy level of the students whoare studying at banking and finance department. For this purpose, a questionnaire was applied to thestudents at the department of banking and finance in Manisa Celal Bayar University. Thequestionnaire was also applied to other students who were referred to as the control group. Thecontrol group consists of students who have not previously studied accounting and finance. Thequestionnaire was answered by 92 students in the banking and finance department and by 95 studentsin the control group. One of the sub-objectives of the study is to compare between banking and financestudents and control group. Thus, the existence of accounting and finance literacy in these studentswill be analyzed in a healthier way. According to the survey findings, while the financial literacy ofthe students studying in the banking department is acceptable, but it cannot be said that the sameresults are valid for the accounting literacy of these students.

Bu çalışmanın amacı bankacılık ve finans bölümünde okumakta olan öğrencilerin muhasebe ve_x000D_ finansman okuryazarlık seviyesini ölçmeye çalışmaktır. Bu amaçla, söz Manisa Celal Bayar_x000D_ Üniversitesi bankacılık ve finans bölümünde okuyan öğrencilerine yönelik bir anket uygulanmıştır. Söz_x000D_ konusu anket aynı zamanda kontrol grubu olarak alan dışı olan öğrencilere de uygulanmıştır. Kontrol_x000D_ grubu daha önce muhasebe ve finans dersi almamış olan öğrencilerden oluşmaktadır. Anket_x000D_ bankacılık ve finans bölümünde 92, kontrol grubunu oluşturan alan dışında ise 95 olmak üzere_x000D_ toplamda 187 öğrenciye uygulanmıştır. Çalışmanın alt amaçlarından biri de bankacılık ve finans_x000D_ bölümü öğrencileri ile kontrol grubunu karşılaştırmaktır. Böylelikle söz konusu öğrencilerdeki_x000D_ muhasebe ve finansman okuryazarlığının olup olmadığı daha sağlıklı bir şekilde analiz edilebilecektir._x000D_ Anket bulgularına göre finansal okuryazarlık bankacılık ve finans bölümü öğrencilerinde kabul_x000D_ edilebilir bir seviyedeyken, buna karşılık aynı sonuçlar muhasebe okuryazarlığı için geçerli değildir.
Muhasebe ve Finans Okuryazarlığı: Karşılaştırmalı Bir Çalışma